Comparative evaluation of electrocoagulation and endo-clip haemostasis techniques in laparoscopic ovariohysterectomy in female dogs - Fagana, Hemant Kumar; Tanwar, Mahendra; Palecha, Sakar; Bishnoi, P. (Indian Journal of Veterinary Surgery, 2025)
The study was conducted on 12 female dogs of varying ages and body weights, randomly allocated into two groups (6 animals in each group) based on the haemostasis technique used during laparoscopic ovariohysterectomy. In group I, electrocoagulation was performed, and in group II, endo-clip application was done. The mean total surgical duration for laparoscopic ovariohysterectomy was 39.33±0.80 min in group I and 51.17±0.75 min in group II, indicating a shorter operative time with the electrocoagulation technique. Both haemostasis techniques were found to be effective and feasible in nulliparous and lean animals. However, in pluriparous and overweight (fatty) female dogs, only the electrocoagulation technique provided consistently reliable outcomes, suggesting that it may be more suitable in such cases due to better tissue handling and haemostatic efficacy.